APLIKASI ADMINISTRASI ONLINE BERBASIS ANDROID MENGGUNAKAN GOOGLE APPS SEBAGAI SARANA PELAYANAN MASYARAKAT DITENGAH PANDEMI COVID19 - Zaliluddin, Dadan (Universitas Serang Raya, 2021)
Abstract— The COVID-19 pandemic measures to prevent the spread of the coronavirus include travel restrictions, quarantines, imposition of curfews, event delays and cancellations, and facility closures. Various national border closures or restrictions on incoming passengers, screening at airports and train stations, as well as travel information about areas with local transmission In terms of village administration services under normal circumstances, physical contact cannot be avoided for administrative settlement, for that the role of information technology in an agency is very much needed because technology is very developed in today's era. This can reduce physical contact but administrative settlements continue to run smoothly, advances in science and technology that support computerization are important in assisting daily work activities. Almost all fields require a computer as a tool, because it has advantages, namely in terms of accuracy and in terms of performance in data processing. Not only that, Mobile Applications also have services such as language processing, artificial intelligence, and standard programs at work. Anyway a service that doesn't require you to be physically in front of hardware like computers and laptops. The village is an organization and as the smallest part of the administrative government system in Indonesia, is required to be able to follow technological developments and continue to improve its ability to manage village population administration data. Keywords— Village, Administration, Covid-19, Android.